Beyond a Boundary: Washington’s Historic Districts and Their Racial Contents - Logan, Cameron (Urban History Review / Revue d'histoire urbaine, 2012)
Between the mid-1970s and the mid-1980s there was a wave of citizen-initiated preservation activity in Washington, DC, much of it directed towards identifying and expanding neighbourhood historic districts. These efforts were driven by several different events and influences that coalesced in the period: a new sense of local control that came with the establishment of municipal self-government in the District of Columbia after 1975; the expectation that a comprehensive historic preservation law would be enacted in the district; the U.S. Supreme Court’s affirmation of the legality of preservation controls in 1978; and the renewed salience of the idea of place that affected everything from community art and neighbourhood activism to urban design and architectural theory. This paper addresses this moment of intense activity by investigating the ways in which preservation advocates in one neighbourhood, Dupont Circle, sought to expand their historic district. The proposal to add several square miles of new territory to the designated historic area was led by a predominantly white preservation organization, the Dupont Circle Conservancy. The proposal aroused significant opposition from a group calling itself the 14th and U Street Coalition, which styled itself as the representative of African-American interests and historical identity in neighbouring Shaw. They protested that the Dupont Circle preservationists were attempting to annex their neighbourhood and with it, their history. At first glance this conflict appears to be a predictable case of inner city gentrification fought along the lines of racial identity. But when examined more carefully, the series of claims and counter-claims embedded in the conflict exposed a more nuanced set of issues related to skin tone, class, and historical entitlement. The conflict highlighted the absence of any agreement about what constituted the historicity of such a historic area and cast doubt over who might be qualified speak on behalf of the history contained in such an area.